Keep the Waste Out of Your Space: Creating a Greener World and a Healthier Place - Akbar Ilham Pamungkas; Rashid Rahman (Yayasan Adra Karima Hubbi, 2026)
Background. Urbanization and industrial activities have increased waste generation, leading to environmental degradation and negative health impacts. Proper waste management in personal and communal spaces is critical for promoting sustainability, reducing pollution, and improving human well-being. Despite awareness campaigns, the adoption of effective waste reduction and recycling practices remains inconsistent, highlighting the need to understand factors influencing individual and community behavior toward waste management. Purpose. This study aimed to explore strategies for reducing waste in living and working spaces and to assess their impact on environmental sustainability and human health. Specifically, it investigated how organized waste management practices, recycling initiatives, and behavioral interventions contribute to creating greener and healthier environments. Method. A mixed-methods approach was employed, involving surveys of 350 urban residents, observations of household and office waste management practices, and interviews with sustainability experts. Quantitative data were analyzed using descriptive statistics and correlation analysis, while qualitative responses were coded thematically to identify common practices, challenges, and motivators. Results. The findings indicate that consistent waste segregation, adoption of reusable materials, and community-led recycling programs significantly reduce environmental impact and improve perceived cleanliness and health outcomes. Educational interventions and visible waste management infrastructures were positively correlated with higher participation rates. Conclusion. Effective waste management in personal and communal spaces can substantially contribute to environmental sustainability and public health. Policy makers and educators should prioritize awareness campaigns, accessible recycling infrastructure, and behaviorally-informed strategies to enhance waste reduction practices in urban settings.